2023
DOI: 10.3390/jcm12031135
|View full text |Cite
|
Sign up to set email alerts
|

Allograft and Autologous Reconstruction Techniques for Neglected Achilles Tendon Rupture: A Mid-Long-Term Follow-Up Analysis

Abstract: Achilles tendon ruptures that are not immediately recognized and treated are sometimes diagnosed as delayed injuries and may require different surgical repair options based on gap size. The potential complications associated with using an allograft for reconstruction may lead some surgeons to prefer the use of autologous techniques. However, allografts are often considered a salvagement option when large defects are present. In this study, we examined the long-term clinical outcomes and complications of 17 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…For such defects, Haraguchi et al were some of the first to note success in treating >5-cm defects utilizing calcaneal bone block allografts-similar to the one employed in our approach 5,11 . In a recent series of large segment Achilles defects (>6 cm) treated by bone block allograft, Jimenez-Carrasco et al showed sustained improvement in ATRS and Academy of Foot and Ankle Surgeons scores at nearly 5 years postoperatively, although they note a prolonged need for weightbearing restriction for bone block incorporation 12 . Similarly, Cenfuegos and Song each report success utilization of a bone block allograft to bridge 12-cm Achilles defects-with bone block incorporation at 1 year-and noted their patient was able to return to preinjury activity 1 year after surgery 13,14 .…”
Section: Discussionmentioning
confidence: 99%
“…For such defects, Haraguchi et al were some of the first to note success in treating >5-cm defects utilizing calcaneal bone block allografts-similar to the one employed in our approach 5,11 . In a recent series of large segment Achilles defects (>6 cm) treated by bone block allograft, Jimenez-Carrasco et al showed sustained improvement in ATRS and Academy of Foot and Ankle Surgeons scores at nearly 5 years postoperatively, although they note a prolonged need for weightbearing restriction for bone block incorporation 12 . Similarly, Cenfuegos and Song each report success utilization of a bone block allograft to bridge 12-cm Achilles defects-with bone block incorporation at 1 year-and noted their patient was able to return to preinjury activity 1 year after surgery 13,14 .…”
Section: Discussionmentioning
confidence: 99%
“…However, studies focusing on the surgical management of CATR were reviewed, specifically those with evidence levels A to D. The researchers carefully analyzed the inclusion criteria of the identified studies to observe and determine the surgical indications for CATR. Following the above search strategy, 16 studies were included [33,[56][57][58][59][60][61][62][63][64][65][66][67][68][69][70], of which 1 study was grade A [56], 1 study was grade B [57], 6 studies were grade C [33,[58][59][60][61][62], and 8 studies were grade D [63][64][65][66][67][68][69][70]. The most common conditions for which surgical management is indicated were CATR patients exhibiting signs of functional limitation, such as pain or tenderness, inability to execute a single heel raise, or repetitive single-leg heel raise endurance exercises, as well as difficulty in walking and ascending stairs, along with ankle swelling; these symptoms were accompanied by positive results in the call squeeze and knee flexion [71], and their diagnoses were confirmed through MRI or ultrasound examinations (16 studies).…”
Section: What Are the Indications For Surgical Treatment Of Catr?mentioning
confidence: 99%